Pengaruh Media Sosial, Celebrity Endorser, dan Online Customer Review Terhadap Keputusan Pemblian Produk Kosmetik Pinkflash di Kabupaten Dompu - Winanda, Tri; HS, Rusminah (Postgraduate, University of Mataram, 2024)
This research aims to test and analyze the influence of Social Media, Celebrity Endorser, and Online Customer Reviews on the Purchasing Decisions of Pinkflash Cosmetic Products in Dompu Regency. The population in this study were people in Dompu Regency who had purchased Pinkflash cosmetic products. The sample in this study consisted of 94 respondents. The sampling technique employed in this research was non-probability sampling using purposive sampling method. Data analysis in this study utilized multiple linear regression analysis, and all data were processed using SPSS Statistics 25. The results of testing and statistical data analysis indicated that the indicators in the study were valid, where in the classic assumption test, the data were normally distributed and there was no multicollinearity. The results of this study indicate that Social Media and Online Customer Reviews have a positive and significant influence on Purchasing Decisions, while Celebrity Endorser does not have a significant influence on Purchasing Decisions.